CONTROLLED RELEASE FERTILIZER AND CONTAINER VOLUME IMPROVE THE SEEDLING MORPHOPHYSIOLOGY OF Lonchocarpus muehlbergianus HASSL. - Roubuste, Roberta Rodrigues; Saldanha, Cleber Witt; Missio, Evandro Luiz; Araujo, Maristela Machado; Gasparin, Ezequiel; Maldaner, Joseila (Floresta, 2025)
The aim of this study was to evaluate the effect of different container volumes and controlled-release fertilizer (CRF) concentrations on the growth of Lonchocarpus muehlbergianus seedlings produced in a nursery. The used experimental design was of randomized blocks with split plots, in a factorial scheme (2x5), with two container volumes (100 and 175 cm³) and five CRF concentrations (0, 3, 6, 9 and 12 g L-1), with six replicates. The data were subjected to analysis of variance (ANOVA) and, when significant, were compared by Tukey’s test (p<0.05) or polynomial regression. At 180 days after the seedling emergence, the following attributes were evaluated: height (H), stem diameter (DC), H/SC ratio, shoot dry mass (MSPA), root dry mass (MSRA), Dickson’s quality index (DQI), relative chlorophyll content (ICF), chlorophyll a and b and carotenoid content and chlorophyll a fluorescence. The species is responsive to fertilization as well as to the container volume, obtaining superior results when produced in 175 cm³ and the addition of 9.6 to 12 g L-1 of CCRF, as they generally provide the highest averages for the morphophysiological variables analyzed, enabling seedlings with commercial quality and faster shipment from the nursery.